2002
DOI: 10.1039/b207869d
|View full text |Cite
|
Sign up to set email alerts
|

Anion exchanger as a reaction/separation medium—absorptiometric determination of trace amounts of boron in waters by on-line complexation with chromotropic acid presorbed on the anion-exchange column

Abstract: A novel method of on-line absorptiometric determination for trace amounts of boron was developed based on the complexation with chromotropic acid presorbed on an anion-exchange column. On-line reaction and separation were achieved by controlling pH conditions in solutions to accelerate the 1:2 complex formation in the concentration process at pH 3 and to stabilize the complex in the separation process at pH 8. About 75% of the boron introduced into the stream was kinetically collected as the 1:2 complex on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…The latter method, however, exhibits better precision as indicated by lower standard deviation. Shao et al [2] and Motomizu et al [18] reported the concentration of boron in tap and river water to occur in the range of 5…”
Section: Application Of the Ccts-nmdg Resin For Boron Collection In Wmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter method, however, exhibits better precision as indicated by lower standard deviation. Shao et al [2] and Motomizu et al [18] reported the concentration of boron in tap and river water to occur in the range of 5…”
Section: Application Of the Ccts-nmdg Resin For Boron Collection In Wmentioning
confidence: 99%
“…Water contamination by boron is one of the widespread environmental problems, since even a few parts per million present in irrigation water can cause stunting of plant growth. Increasing attention has also been paid to microelectronic industries since the existence of trace amounts of boron in ultrapure water for cleaning and etching process can seriously influence the characteristics of semiconductor [2][3]. These facts show that the removal of ultra-trace, trace or large amount of boron is still a challenging problem, although a boron-specific resin was introduced in the mid-1960`s.…”
Section: Introductionmentioning
confidence: 99%
“…5 Also, the detection limit can be further lowered by introducing a larger volume of the sample solution, as mentioned in our earlier report. 14 Overall, the proposed method can be used to determine trace amounts of boron with high precision and accuracy in steel samples.…”
Section: Determination Of Steel Samplesmentioning
confidence: 99%
“…10 In our previous studies on the complexation of boric acid with chromototropic acid (4,5-dihydroxy-2,7-naphthalene disulfonic acid), an on-line UV absorptiometric system for the 1:2 complex was designed using an anion-exchange column and successfully applied to the determination of ultra-trace amounts of boron in water. 14 In this study, the applicability of our method to the determination of trace amounts of boron in steel was examined.…”
Section: Introductionmentioning
confidence: 99%
“…20 These properties make it possible to utilize a cation-exchange column as a reaction/concentration/separation medium in a highperformance liquid chromatography (HPLC) system; this idea was originally developed by our laboratory for the on-line trace analysis of boron using chromotropic acid as a complexing reagent. 21 For the Cr(VI) determination method, the DPC has no absorption at 540 nm, at which the complex has strong absorption. DPC can be concentrated on a short column by hydrophobic interaction.…”
Section: Introductionmentioning
confidence: 99%